Adverse Drug Reactions Among End-Stage Renal Failure Patients ec Diabetes Mellitus in General Hospital Pulau Pinang-Malaysia - Fitria, Najmiatul; Gillani, Syed Wasif (Jurnal Farmasi Andalas, 2013)
Our study aimed at evaluating Adverse Drug Reactions (ADRs) among chronic kidney disease patients at the End-Stage Renal Failure (ESRF) secondary to Diabetes Mellitus. Retrospective cross-sectional study was used as the method of this study..Naranjo Scale was used to observe ADRs amongÂ  patients. Statistical analysis was done using statistical package of social sciences (SPSS 17Â®). Ethical clearance was done with respective clinical research committee. Study findings presents from 200 patients, 5.5% have probable, 15% possible and 79.5% doubtful ADRs. Hypoglycemia (2.5%) had the highest number of probable ADR. Insulin (1.5%) and gliclazid (1%) were the major cause of probable ADRs. Analysis showed significant correlation (sig.<0.05) between age and ESRF secondary to diabetes mellitus. Patient with ESRF secondary to diabetes mellitus above 55 years are tend to have ADRs. Analysis also showed no significant correlation (sig.>0.05) between adverse drug reactions and ESRF patients secondary to diabetes mellitus.Â